A Proposed Path to Bridge the Gap Between Information Behaviour Research and Professional Practice. Issue 1 (2nd January 2023) - Afzal, Waseem
ABSTRACT: A research culture that fosters communication and collaboration between academics and professionals is vital for creating a flourishing and well-informed scholarly and professional community. Within the library and information science field, a gap between research and professional practice is well-documented. This gap has also been noted in the sub-field of information behaviour. This paper contends that the time is ripe now to take some steps to fill this gap by (a) first refocusing on information behaviour embodying more than seeking and searching for information, (b) synthesising and advancing research concerning the impacts of different information behaviours on users' thinking, emotions, feelings, and actions, (c) undertaking research where academics and information professionals can jointly study the relationship between information services, information behaviours, and users, and (d) reducing the barriers in communicating research between researchers and professionals. Hopefully, academics and professionals will embrace these considerations and work more closely to reduce the gap between information behaviour research and professional practice.